THE CORRELATION BETWEEN CONSUMPTION OF BRAIN ROT CONTENT AND STUDENTS’ LEARNING CONCENTRATION - Dewi, Melyana (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
Brain rot refers to the habitual consumption of short, fast, and repetitive digital content that prioritizes entertainment over meaningful cognitive engagement. This pattern is widely found on platforms such as TikTok, YouTube Shorts, and Instagram Reels, particularly among vocational high school students. This study examines the relationship between brain rot content consumption and learning concentration at SMKN 1 Belimbing. Using a quantitative correlational design, data were collected from 150 students through validated questionnaires. Statistical analysis using the Pearson Product-Moment test showed a moderate and significant correlation between brain rot consumption and decreased learning concentration (r = 0.464, p < 0.01). The coefficient of determination (R² = 0.215) indicates that 21.5% of the variation in learning concentration is explained by students’ consumption of brain rot content. These findings demonstrate that excessive exposure to short-form entertainment content plays a meaningful role in reducing students’ ability to sustain focus. The study contributes to the growing understanding of digital behavior’s cognitive impact in vocational education and highlights the importance of digital literacy and regulated social media use. Future research should consider additional variables such as motivation, mental health, and family support to provide a more comprehensive explanation of factors influencing learning concentration.